UJI AKTIVITAS ANTIOKSIDAN KOMBINASI INFUSA BIJI ALPUKAT (Persea americana) DAN BIJI PEPAYA (Carica papaya L.) TERHADAP TIKUS PUTIH (Rattus norvegicus) DIABETES MELLITUS DENGAN PARAMETER MDA - Rahman, Safriani; Kosman, Rachmat; Sudrianto, Sudrianto (Fakultas Farmasi UMI, 2015)
This research aims to determine the concentration Infusa Seeds Avocado and papaya seeds effective leaves that have antioxidant activity to MDA levels in diabetic mellitus with rats was induced with alloxan. This research used 21 white rats were divided into 7 groups. All rats were induced by alloxan 110 mg/KgBB intraperitoneally. Group I as a normal control,group II was administered with Na.CMC as a negative control, group III avocado seed infusion of 10%, group IV papaya seed infusion of 10%, group V infusion combination of avocado seeds and papaya seeds 4%v/v, group IV infusion combination of avocado seeds and papaya seeds 6%v/v, group VII infusion combination of avocado seeds and papaya seeds 8%v/v. Administration were given orally for 14 days orally. Before treatment, all groups except the group I was induced with alloxan 110 mg/kgBB in intraperitonially. Measurement of MDA levels before and after administration of infusion. MDA levels as measured on a spectrophotometer 532 nm wavelength. MDA Assay performed with TBA method. The results showed that the combined infusion of avocado seeds and papaya seeds, concentrations of 4%v/v, 6%v/v, 8%v/v effective as an antioxidant.